The Conflict between Philanthropinism and Humanism and the Place of Philosophy in the Whole of Knowledge - Mancebo Pérez, Pilar (Logos. Anales del Seminario de Metafísica, 2023)
On the basis of the Husserlian assertion of the philosophical crisis as the vital crisis that has diverted the humankind from his télos, by establishing the techno-scientific model of world domination, this article researches the place of philosophy in the educational system by exploring the reforms proposed in Bavaria and Prussia by Niethammer and Humboldt at the very beginning of the 19th century. Both reforms, each in a different way, incorporated philosophy to a State-education whose aim was to raise the human being to his humanity, facing the philanthropinism’s utilitarian claims. In this sense, the article turns towards the humanist concept of formation (Bildung), to which both reforms are devoted, and to which Gadamer returns in Truth and Method, where it is seen as an ideal, in order to face the universality-claim of the modern science in relation to the notions of knowledge and truth, as well as in order to think the ontological horizon of hermeneutical experience. Precisely this ideal enables us to find the place of philosophy in the whole of knowledge and to lead the human being to his humanity.